IBN KHALDŪN’S BIOGRAPHY: UNVEILING GLOBAL HISTORY AND THE SOCIOLOGY OF MODERN CIVILIZATION - Merican, Ahmad Murad (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2022)
Ibn Khaldūn and his Muqaddimah is a continuing project on the European intellectual map. For a long time, most of his works was studied by the French. The same cannot be said of the Malaysian intellectual Malaysian landscape. Ibn Khaldūn, of course, makes an attractive option for academic courses and readings in a variety of disciplines. This essay attempts to recast Ibn Khaldūn in the Malaysian intellectual landscape viz discourses on global history and approaching the study of civilization from a sociological and historical perspective. The sentiment echoes more of the Western engagement with the polymath. Malaysian university campuses are ambivalent. The Khaldunian corpus is almost non existent. The West has attempted to modernize Ibn Khaldūn. Some have construed this as “denaturing” him, accusing the thinker of “anticipatory plagiarism.” The Muslim world has been subdued in defending such accusations against him. There is no worthy defence. This essay uses the framework from Robert Irwin in his Ibn Khaldun: An Intellectual Biography. We ask who was Ibn Khaldūn writing for? For the state and authority? Or for himself? Some of the earliest beneficiaries of the Khaldunian corpus was the Ottoman state. This essay notes the disconnect between Ibn Khaldūn and the practice of modern history and social science. The Muqaddimah has largely been ignored as course or as text in the various social science disciplines. The corpus is not seen as providing an alternative form of knowledge. Irwin, however, provides a critical examination of Ibn Khaldūn’s magnum opus, and the political and intellectual climate that he thrived on. As a scholar, Ibn Khaldūn was partisan and certainly close to political institutions. Objective and universal knowledge is not blind to the human condition. Even when deciding to take a reprieve in writing, he sought the protection of a powerful tribe in the hinterland, the Awlad ‘Arif in what is now western Algeria. This essay serves as a contribution to the discourse on the Khaldunian history and sociology.